2010
DOI: 10.1038/sj.bjc.6605627
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen resistance in early breast cancer: statistical modelling of tissue markers to improve risk prediction

Abstract: BACKGROUND: For over two decades, the Nottingham Prognostic Index (NPI) has been used in the United Kingdom to calculate risk scores and inform management about breast cancer patients. It is derived using just three clinical variables -nodal involvement, tumour size and grade. New scientific methods now make cost-effective measurement of many biological characteristics of tumour tissue from breast cancer biopsy samples possible. However, the number of potential explanatory variables to be considered presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Although VPA has been shown to reduce cancer proliferation to some extent, data about its effect on breast cancer cells are still insufficient in both animals and humans, and studies have often yielded contrasting results and conflicting conclusions (Dutertre et al, 2010;Adams et al, 2010;Baneshi et al, 2010). The inhibitory effect of VPA may be cancer type-specific in many studies; for example, one study found no difference in invasiveness between treated and untreated bladder cancer cell lines HTB5 and HTB9 (Byun et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although VPA has been shown to reduce cancer proliferation to some extent, data about its effect on breast cancer cells are still insufficient in both animals and humans, and studies have often yielded contrasting results and conflicting conclusions (Dutertre et al, 2010;Adams et al, 2010;Baneshi et al, 2010). The inhibitory effect of VPA may be cancer type-specific in many studies; for example, one study found no difference in invasiveness between treated and untreated bladder cancer cell lines HTB5 and HTB9 (Byun et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Along with this recent literature there is information that women are overweight effectiveness of systemic treatments may be lower than expected. Other data refute this information [3].…”
Section: Introductionmentioning
confidence: 82%
“…Implicit in this mechanism for resistance is cross-talk activation between the ER and the epidermal growth factor receptor (EGFR/ Her-2/neu) pathways [3]. Treatment with various signal transduction inhibitors has been used in combination with endocrine therapy to overcome resistance, such as gefitinib, which targets the internal tyrosine kinase domain of EGFR, and trastuzumab, which blocks the external domain of Her-2/neu [4].…”
Section: Introductionmentioning
confidence: 99%
“…Of them, tumor size and nodal status are clearly among the strongest predictors of overall survival and metastasis and are also strong predictors of postmastectomy chest wall relapse when radiation is not used [1,2] . However, the outcomes of numerous studies correlating clinical and pathologic features of the primary tumor and/or nodal disease with prognosis have not been uniformly reported [3][4][5][6][7][8][9][10][11] . For example, the presence of multicentric disease is strongly associated with other risk factors for local-regional recurrence, such as tumor size and nodal involvement, but in patients with stage II disease with 0-3 positive lymph nodes, multicentric disease does not seem to elevate the risk of local-regional recurrence [12] .…”
Section: Introductionmentioning
confidence: 99%